Sam : a novel [large type] - Goodman, Allegra (Thorndike Press large print basic, 2023)
"What happens to a girl's sense of joy and belonging--to her belief in herself--as she becomes a woman? This unforgettable portrait of coming-of-age offers subtle yet powerful reflections on class, parenthood, addiction, lust, and the irrepressible power of dreams. "There is a girl, and her name is Sam." So begins Allegra Goodman's moving and wise new novel. Sam is seven years old and living in Beverly, Massachusetts. She adores her father, though he isn't around much. Her mother struggles to make ends meet, and never fails to remind Sam that if she studies hard and acts responsibly, adulthood will be easier--more secure and comfortable. But comfort and security are of little interest to Sam. She doesn't fit in at school, where the other girls have the right shade of blue jeans and don't question the rules. She doesn't care about jeans or rules. All she wants to climb. Hanging from the highest limbs of the tallest trees, scaling the side of a building, Sam feels free. As a teenager, Sam begins to doubt herself. She yearns to be noticed, even as she wants to disappear. When her climbing coach takes an interest in her, his attention is more complicated than she anticipated. She resents her father's erratic behavior, but she grieves after he's gone. And she resists her mother's attempts to plan for her future, even as that future draws closer. The simplicity of this tender, emotionally honest novel is what makes it so powerful. Sam by Allegra Goodman will break your heart, but will also leave you full of hope"--